2022
DOI: 10.1093/jn/nxac118
|View full text |Cite
|
Sign up to set email alerts
|

Combined Supplementation with Arachidonic and Docosahexaenoic Acids in T Helper Type-2 Skewed Brown Norway Rat Offspring is Beneficial in the Induction of Oral Tolerance toward Ovalbumin and Immune System Development

Abstract: Background A T helper type-2 (Th2) skewed immune response is associated with food allergies. Docosahexaenoic (DHA) and arachidonic acid (ARA) have been shown to promote oral tolerance (OT) in healthy rodents. Objectives To study the effect of combined ARA + DHA supplementation during suckling and weaning period on OT and immune system development in Th2 skewed Brown Norway rat offspring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…35 Numerous studies have reported that dietary nutrients alleviate food allergic symptoms through regulating the Th1/Th2 balance. 36,37 RA has been widely reported to relieve allergic symptoms through regulating the balance of Th1/Th2 cytokines in atopic dermatitis, allergic rhinitis, asthma and so forth. 19,38 Interestingly, the expressions of IL-4 and IL-5 were markedly upregulated in the mice of the model group, but significantly decreased by oral administration of RA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Numerous studies have reported that dietary nutrients alleviate food allergic symptoms through regulating the Th1/Th2 balance. 36,37 RA has been widely reported to relieve allergic symptoms through regulating the balance of Th1/Th2 cytokines in atopic dermatitis, allergic rhinitis, asthma and so forth. 19,38 Interestingly, the expressions of IL-4 and IL-5 were markedly upregulated in the mice of the model group, but significantly decreased by oral administration of RA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐5 is a key cytokine responsible for eosinophil activation in allergic inflammation 35 . Numerous studies have reported that dietary nutrients alleviate food allergic symptoms through regulating the Th1/Th2 balance 36,37 . RA has been widely reported to relieve allergic symptoms through regulating the balance of Th1/Th2 cytokines in atopic dermatitis, allergic rhinitis, asthma and so forth 19,38 .…”
Section: Discussionmentioning
confidence: 99%
“…An OVA-sensitized mouse model supplemented with olive oil had a reduction in allergic symptoms, with a reduction in cytokines associated with Th2 cells and an increase in cytokines released by Treg cells [132]. The combined supplementation with arachidonic and docosahexaenoic acids during suckling period presented beneficial effects on OVA oral tolerance of the rat offspring, revealing that this combination decreased Th2 immune response due to an increase in Th1 cytokine levels [133]. A meta-analysis study concluded that omega-3 supplementation during pregnancy reduces the risk of FA in children.…”
Section: Dietary Supplementsmentioning
confidence: 97%
“…Olive oil: FA animal model [132]. Arachidonic and docosahexaenoic acids (PUFAs): mother during suckling period levels [133]. Omega-3 supplementation: mothers during pregnancy [134].…”
Section: Dietary Supplementsmentioning
confidence: 99%